Second Nature: Adorno and Contemporary Education - Edvardas Šumila (Acta Paedagogica Vilnensia)
The paper aims to provide a conceptual basis for reconciling the radical resistance to totality posed by Adorno’s negative dialectics with contemporary considerations of the environment, capable of developing a more symbiotic educational approach in the context of contemporary crises. This is done by exploring the notion of ‘second nature’, the significance of which is underlined by its rootedness in the dialectical tradition of German philosophy and Adorno’s emphasis on the nonidentical as an essential condition for critique and a link between subjectivity and what is understood as nature and history.